FOREIGN LANGUAGE READING IN THE US: MAKING READING INSTRUCTION COMMUNICATIVE. - Chandler, Paul Michael (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Foreign/L2 reading in the United States has evolved during the 1990s with the widespread acceptance of the interactive theory of reading. Nevertheless, the communicative language teaching approach often translates into a reduced role for reading in the classroom, and many traditional pedagogical materials are still used in language programs around the US. To foment communicative reading instruction, this paper provides an overview of some of the unique features presented in six currently used language methodology texts, providing a snapshot of how reading instruction is taught to future teachers. Finally, a framework for presenting reading through communicative activities is suggested, one which is both information- and task-based, allowing for easy adjustment to learners´ needs